PENGEMBANGAN APLIKASI MODUL INTERAKTIF KOMPUTER DAN JARINGAN DASAR BERBASIS ANDROID - Seventina Agusty; Vera Irma Delianti (Universitas Negeri Padang, 2019)
Educational goal is for improving the quality of human resources, forming character and developing the potential of students to become useful human beings for the nation and the society . to achieve these educational goals, the quality of education must be improved through learning facilities and the learning process. Based on researcher observations at Vocational school 6 Padang, especially on computer subjects and basic networks, it was found teachers have not used interactive modules when learning activities. this affects the student learning outcomes which are still many that have not reached the minimum criteria standard (KKM)ṫhe design of this interactive module application aims to produce learning media that make it easier for students to learn computer subject matter and basic networks wherever they are. the design of this application uses Prototyping development method with android-based java programming with Android Studio application software (version 3.3) with Gradle 4.4. This research produces an interactive computer application module and basic network based on Android, the features that exist in this interactive module application are learning material, videos, and exercises that are in accordance with the learning material in the 2013 curriculum. this can facilitate users in understanding computer and basic network material.Keywords: interactive modules, learning media, computers and basic networks.